Single-Stranded Phosphorothioated Regions Enhance Cellular Uptake of Cholesterol-Conjugated siRNA but Not Silencing Efficacy - Socheata Ly; Dimas Echeverria; Jacquelyn Sousa; Anastasia Khvorova (Elsevier, 2020)
Small interfering RNAs (siRNAs) have potential to silence virtually any disease-causing gene but require chemical modifications for delivery to the tissue and cell of interest. Previously, we demonstrated that asymmetric, phosphorothioate (PS)-modified, chemically stabilized, cholesterol-conjugated siRNAs, called hsiRNAs, support rapid cellular uptake and efficient mRNA silencing both in cultured cells and in vivo. Here, we systematically evaluated the impact of number, structure, and sequence context of PS-modified backbones on cellular uptake and RNAi-mediated silencing efficacy. We find that PS enhances cellular internalization in a sequence-dependent manner but only when present in a single-stranded but not double-stranded region. Furthermore, the observed increase in cellular internalization did not correlate with functional silencing improvement, indicating that PS-mediated uptake may drive compounds to non-productive sinks. Thus, the primary contributing factor of PS modifications to functional efficacy is likely stabilization rather than enhanced cellular uptake. A better understanding of the relative impact of different chemistries on productive versus non-productive uptake will assist in improved design of therapeutic RNAs.